High-purity 1,2-dimyristoyl-sn-glycero-3-phosphocholine: synthesis and emulsifying performance evaluation - Kim, Se-Young; Park, Ye-Lim; Ji, Ha-Eun; Lee, Hae-Se; Chang, Hyeon-Jun; Bang, Gyeong-Hee; Lee, Jeung-Hee (Frontiers in Nutrition, 2024)
Emulsions, particularly oil-in-water ones, are widely used for the oral delivery of bioactive lipophilic substances through timepoint-specific release based on digestibility modulation and are well suited for large-scale industrial production. However, the thermodynamic instability of emulsions, manifested by their tendency to phaseseparate, necessitates the use of emulsifiers as stabilizing agents. This study describes a new and more efficient synthetic route to a potentially industrially important emulsifier, 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), and compares its ability to stabilize oil-in-water emulsions with that of a well-established industrial emulsifier, soybean lecithin, revealing the superiority of the former. In vitro digestion experiments are used to examine the behaviors of DMPC-and soybean lecithin-stabilized emulsions in the gastrointestinal tract and thus model the release of encapsulated bioactive compounds from these emulsions. We believe that our study makes a significant contribution to the literature because it paves the way for the cost-effective production of DMPC and demonstrates its potential for food and pharmaceutical industry-related applications.Further, we believe that this paper will be of interest to the readership of your journal because it describes a new and more efficient synthetic route to DMPC, which is not a nutraceutical itself but is an important component of emulsion-based nutraceutical delivery systems. Given that one of the subcategories of the present research topic is Delivery systems of nutraceuticals into the body for various purposes to overcome low bioavailability, slow absorption, or excessively rapid excretion, our study fits the scope of the above topic.